(untitled) (Journal of Nepal Geological Society, 2024)
Landslides pose a persistent and severe risk, frequently resulting in substantial harm to both people and infrastructures in Nepal. Understanding the underlying cause-and-effect dynamics of these events is crucial for effective mitigation measures to minimize their impacts. This research delves into assessing the susceptibility to landslides in the Thaha, Bhimphedi, Kailash, and Indrasarobar Rural Municipalities of the Makawanpur district. Considering the area’s predisposition to landslides and soil erosion, exacerbated by the highly dissected topography and monsoon rainfall, this region is critically important for landslide susceptibility mapping. Using the satellite and aerial images, an inventory of 230 landslides was prepared. A total of nine landslide influencing factors including slope, aspect, curvature, distance to road, distance to stream, landuse/landcover, topographic position index, lithology, and lineament density were integrated to produce the landslide susceptibility index using the Analytic Hierarchy Process (AHP). Landslide susceptibility map thus generated was divided into five classes ranging from very low to very high susceptible zones. Validation of the susceptibility map was done using the landslide inventory, where the area under the Receiver Operating Characteristic (ROC) curve indicated a success rate of 0.727, demonstrating a commendable accuracy in predicting landslide occurrences. Similarly, the landslide density along with different susceptibility classes also indicate better performance to predict the susceptible zone. This susceptibility map can be very useful for planning the effective landslide disaster response and mitigation in the study area.